2014
DOI: 10.1266/ggs.89.99
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory divergence of X-linked genes and hybrid male sterility in mice

Abstract: Postzygotic reproductive isolation is the reduction of fertility or viability in hybrids between genetically diverged populations. One example of reproductive isolation, hybrid male sterility, may be caused by genetic incompatibility between diverged genetic factors in two distinct populations. Genetic factors involved in hybrid male sterility are disproportionately located on the X chromosome. Recent studies showing the evolutionary divergence in gene regulatory networks or epigenetic effects suggest that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 92 publications
(140 reference statements)
0
15
0
Order By: Relevance
“…One explanation for this result is that the X chromosome contains more shared incompatibilities than the autosomes, and the PhyloQTL approach offers higher power than the heuristic method to detect these loci. The X chromosome confers hybrid male sterility between domesticus and musculus through complex regulatory mechanisms that remain unclear (Storchová et al 2004;Good et al 2008bGood et al , 2010Oka et al 2010;Campbell et al 2013;Turner et al 2014;Bhattacharyya et al 2014;Oka and Shiroishi 2014). It is possible that incompatibilities involving the X chromosome differ from purely autosomal interactions in some way that affects the snowball prediction.…”
Section: Discussionmentioning
confidence: 99%
“…One explanation for this result is that the X chromosome contains more shared incompatibilities than the autosomes, and the PhyloQTL approach offers higher power than the heuristic method to detect these loci. The X chromosome confers hybrid male sterility between domesticus and musculus through complex regulatory mechanisms that remain unclear (Storchová et al 2004;Good et al 2008bGood et al , 2010Oka et al 2010;Campbell et al 2013;Turner et al 2014;Bhattacharyya et al 2014;Oka and Shiroishi 2014). It is possible that incompatibilities involving the X chromosome differ from purely autosomal interactions in some way that affects the snowball prediction.…”
Section: Discussionmentioning
confidence: 99%
“…During the long history of life science, much important knowledge has been accumulated by research based on mouse genetics and momentous novel findings have been generated at the frontiers of mammalian biology; for example, it has been experimentally demonstrated using inbred mouse strains that the variability of the X chromosome is a key factor for genetic incompatibility in mammals (reviewed in Oka and Shiroishi, 2014). The study of the t-haplotype is one such area of historic research in the field of mouse genetics, and I believe that there are still many buried treasures to be uncovered within the thaplotype.…”
Section: Discussionmentioning
confidence: 99%
“…Several recent studies have found that expression diverges faster for some genes on the X (in XY taxa) and Z (in ZW taxa) chromosomes than on the autosomes between species [6873]. Faster divergence of sex-linked gene expression is especially strong for genes with sex-biased effects (male-biased effects in XY taxa and female-biased effects in ZW taxa) [69,70,71,74]. However, comparisons of expression patterns in whole tissues may obscure differences in individual cell types.…”
Section: Misregulation As a Mechanism For Hybrid Dysfunctionmentioning
confidence: 99%